PENGARUH RASIO LEVERAGE DAN RASIO AKTIVITAS TERHADAP RETURN ON EQUITY PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tarigan Tua, Notracya B.S. (Jurnal Manajemen dan Bisnis, 2012)
The purpose of this study is to investigate and analyze the effect of the leverage ratio and the ratio of the return on equity activity in the Food and Beverage companies listed in Indonesia Stock Exchange. The study population was all Food and Beverage company to list on the Indonesia Stock Exchange until 2011. Study sample as many as 17 companies. The data used are secondary data collected through documentation techniques. The analysis model used is multiple linear regression. Based on the results of research and discussion, it can be concluded that the leverage ratio and the ratio of significant activity and simultaneous partial to the return on equity in the Food and Beverage companies listed in Indonesia Stock Exchange. Determinant coefficient (R Square) of 0.561. This shows that the return on equity can be explained by the leverage ratio and activity ratio of 56.1%, while 43.9% are explained by other factors.